Deterrence or conformity?—An analysis of digital economy taxpayer compliance behavior based on prospect theory - Jin, Peng; Li, Guiping; Xiong, Weiqing (Frontiers in Psychology, 2022)
Taking the tax evasion of live streamers as a reference case, this paper aims to establish a tax compliance prospect theory model, in which the reference point is determined by the taxpayer’s perceived compliance level. The taxpayer compliance behavior is analyzed from two dimensions of the tax authority’s audit deterrence and the taxpayer’s conformity mentality. We find that both deterrence effect and conformity effect are existing in the taxpayer compliance behavior, which are affected by the tax authority’s enforcement effort. When the enforcement effort is low, the deterrence effect and the conformity effect do not exist, and the taxpayer does not comply at all. When the enforcement effort is moderate, the deterrence effect and the conformity effect coexist and the taxpayer complies partially. Besides, the taxpayer compliance level will not exceed the perceived compliance level, and an increase in the perceived compliance level will prompt the taxpayer to comply more. When the enforcement effort is high, there is only a strong deterrence effect, and the taxpayer completely complies. We use the theoretical analysis result to explain the tax compliance behavior of live streamers and find that it is consistent with the predictions of the model. Finally, we propose some policy recommendations on tax administration in digital economy.